Pondok Pesantren Kauman Lasem di Kawasan Pecinan Lasem sebagai Sumber Belajar Sejarah Lokal - Choiriyah, Masfiatul; Arrazaq, Naufal Raffi; Tasnur, Irvan (Universitas Negeri Gorontalo, 2025)
The Kauman Lasem Islamic Boarding School, located in the Chinatown area of Lasem, holds historical significance. This study aims to analyze the potential of the Kauman Lasem Islamic Boarding School as a source for learning local history. This research employs a qualitative method. The findings indicate that the Kauman Lasem Islamic Boarding School serves as a symbol of harmonization. Integrating its historical aspects into the history curriculum enables students to explore the social, cultural, and religious dynamics of Lasem through a contextual approach. This research is expected to encourage the development of experience-based history learning methods and motivate various parties to preserve historical heritage such as the Kauman Lasem Islamic Boarding School